Particle crushing simulations with improved discontinuous deformation analysis. Issue 7 (30th September 2014) - Wang, Xiao-Bo; Xu, Wen-Jie; Zhang, Bing-Yin; Sun, Qi-Cheng
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – Rock-fill dams are embankments of compacted free-draining granular earth containing an impervious zone. Earth utilized in such dams often contains a high percentage of large particles – hence the term rock-fill. Mass stability of these dams results from friction and particle interactions rather than through a cementing agent binding the particles together. However, high-stress conditions and prolonged exposure to the elements can severely damage rock-fill. Therefore, understanding and modeling rock-fill breakage is important for dam engineering. The purpose of this paper is to improve discontinuous deformation analysis (DDA) techniques for modeling rock-fill breakage, proving the new method using simulations of spherical particle crushing. Design/methodology/approach – This work models rock-fill as bonded ellipsoid particles, and develops an improved DDA method to model the breakage of particle assemblies. The paper starts by describing the principles of three-dimensional DDA for spherical particles, and then derives the submatrices for normal contact, shear contact, and frictional force. The new algorithm incorporates a bond model with a revised open-close iteration algorithm into the DDA method to simulate particle crushing. To validate the improved DDA method, calculated particle contacts and movements are validated against theoretical results. Finally, this work performs a series of point-loading experimental tests for cement ellipsoid particles of both high and low compression strengths, with the test results compared against the results from corresponding DDA simulations. Findings – In particle crushing tests, the force and displacement show an approximately linear relationship until the crushing point, at which point low compression ellipsoid particles split into several large pieces while the high-compression particles break into many small fragments. The DDA simulation results are in good agreement with the crushing tests, demonstrating the validity of the DDA method for solving particle crushing problems. Although the improved DDA model is applicable to rock-fill particle crushing studies, some issues remain, particularly in increasing calculation efficiency and performing large-scale computations and long real-time simulations. Future research should address these issues. Originality/value – A bond model with a revised open-close iteration algorithm is incorporated into the DDA method. The simulated results shed insight into rock-fill crushing mechanisms, an element of concern in engineering practices.